The Implementation of Quizizz-Supported Learning Media to Enhance Achievement and Independent Learning in Basic Beauty Education - Dewani, F.Sekar Hayu; Widowati, Trisnani; Wahyuningsih, Sri Endah (Universitas Negeri Semarang, 2023)
The rapid advancement of technology has led to significant changes in the fields of economy, information, and education. An essential component of education that plays a vital role in fostering technological development is Learning Media. One aspect that can be optimized in the learning process is the use of learning media and evaluation tools. Numerous online platforms, such as the Quizizz application, can currently be utilized as learning media. This study aims to understand the development process, feasibility, and effectiveness of Quizizz as a medium and evaluation tool in Basic Beauty courses.This research employs the Research and Development (R&D) method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The study follows a Quasi-Experimental design with a Two-Group Pretest-Posttest format. The products generated in this study are learning media and evaluation tools for basic beauty education.The results of this study, based on feasibility testing and effectiveness testing of Quizizz as a learning medium for basic beauty, indicate that it is highly feasible according to media experts, educational technology experts, and subject matter experts. Effectiveness testing in the experimental class showed that the media could enhance learning outcomes in the anatomy and physiology of beauty. Student responses regarding learning independence showed high levels of self-directed learning when using the Quizizz application developed as a learning medium for Basic Beauty courses.